2008
DOI: 10.1109/lmwc.2008.922648
|View full text |Cite
|
Sign up to set email alerts
|

A K- to Ka-Band Broadband Doubly Balanced Monolithic Ring Mixer

Abstract: A broadband doubly balanced monolithic ring mixer with a new intermediate frequency (IF) signal extraction method implemented by 0.15 m pHEMT process is presented. The hybrid couplers of the proposed mixer consist of multiple coupled lines and fourfold coupled line Marchand baluns. The use of multiple coupled lines leads to a die size less than 1 1 mm 2 and improves the bandwidth of the mixer. The novel fourfold coupled line allows the extraction of the IF signal directly without any extra low pass filter circ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…The removal and recovery of NO x from nitric acid production waste streams was studied on 13X and mordenite in the late 1960s and early 1970s. , Zhang et al. studied adsorption of NO on copper- and silver-exchanged ZSM-5 and mordenites and found that partially irreversible adsorption takes place. , This phenomenon was later studied on transition-metal-exchanged zeolite A by Wheatley et al for its use in medical applications as NO releasers . Zeolites NaY , and Na-ZSM-5 have been studied for NO x removal from flue gas using PSA.…”
Section: Chemical Separations By Zeolitesmentioning
confidence: 99%
“…The removal and recovery of NO x from nitric acid production waste streams was studied on 13X and mordenite in the late 1960s and early 1970s. , Zhang et al. studied adsorption of NO on copper- and silver-exchanged ZSM-5 and mordenites and found that partially irreversible adsorption takes place. , This phenomenon was later studied on transition-metal-exchanged zeolite A by Wheatley et al for its use in medical applications as NO releasers . Zeolites NaY , and Na-ZSM-5 have been studied for NO x removal from flue gas using PSA.…”
Section: Chemical Separations By Zeolitesmentioning
confidence: 99%
“…The chemical nature of the signaling molecules that trigger hepcidin-mediated changes in iron flux are not yet known. Kidneys, which have high concentrations of iron, have the major function of separating dissolved blood components from excreted metabolites, but the role of the iron in kidneys remains largely unexplored …”
Section: Iron Distribution In Cells and Organsmentioning
confidence: 99%
“…IRP1 domains 3 and 4 are separated by more than 30 Å in the RNA complex, while they are contiguous in c-aconitase. Many of the ligands involved in formation of the [4Fe-4S] cluster in aconitase are part of the cavity that contributes bonds to A 15 and G bases of the IRE−RNA terminal loop . Examination of these structures suggests that direct conversion of the aconitase form of the protein to the RNA binding conformation may not occur.…”
Section: Iron/dioxygen Regulation Of Translationmentioning
confidence: 99%
“…Previously, we have demonstrated new topologies [11][12][13] to realize a compact ring DBM even without an additional IF extraction circuit. However, because of the use of the 180 • hybrid, conversion loss is increased when the ring DBM is operated in an up-converter mode.…”
Section: Introductionmentioning
confidence: 99%